Development and validation of genetic markers for sex and cannabinoid chemotype in Cannabis sativa L. Issue 3 (22nd January 2020) - Toth, Jacob A.; Stack, George M.; Cala, Ali R.; Carlson, Craig H.; Wilk, Rebecca L.; Crawford, Jamie L.; Viands, Donald R.; Philippe, Glenn; Smart, Christine D.; Rose, Jocelyn K. C.; Smart, Lawrence B.
Abstract: Hemp ( Cannabis sativa L.) is an emerging dioecious crop grown primarily for grain, fiber, and cannabinoids. There is good evidence for medicinal benefits of the most abundant cannabinoid in hemp, cannabidiol (CBD). For CBD production, female plants producing CBD but not tetrahydrocannabinol (THC) are desired. We developed and validated high‐throughput PACE (PCR Allele Competitive Extension) assays for C. sativa plant sex and cannabinoid chemotype. The sex assay was validated across a wide range of germplasm and resolved male plants from female and monoecious plants. The cannabinoid chemotype assay revealed segregation in hemp populations, and resolved plants producing predominantly THC, predominantly CBD, and roughly equal amounts of THC and CBD. Cultivar populations that were thought to be stabilized for CBD production were found to be segregating phenotypically and genotypically. Many plants predominantly producing CBD accumulated more than the current US legal limit of 0.3% THC by dry weight. These assays and data provide potentially useful tools for breeding and early selection of hemp. Abstract : The largest market for hemp in the US today is for cannabidiol (CBD). For CBD production, growers desire female plants producing minimal tetrahydrocannabinol (THC). We developed and validated high‐throughput molecular assays to distinguish male from female plants, as well as the cannabinoid chemotype (mostly THC, about equal THC and CBD, or mostly CBD). We found that in all three groups there was the potential to exceed the US legal limit of 0.3% THC, and that there was little effect of environment or cultivar per se on CBD:THC ratio. These assays and data will be useful in hemp breeding and production.